2022
DOI: 10.3233/jnd-220816
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Occurrence of Key Clinical Milestones in Duchenne Muscular Dystrophy in the United States Using Real-World Data

Abstract: Background: Data on the clinical course of Duchenne muscular dystrophy (DMD) exist from well-characterized clinical cohorts but estimates from real-world populations are fewer. Objective: The objective was to estimate the prevalence of key clinical milestones by age, among real-world commercially-insured DMD patients in the US. MarketScan claims (2013–2018) were used to identify males with DMD. Methods: The percentages experiencing loss of ambulation (LOA), scoliosis, neurologic/neuropsychiatric involvement, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Consistent with previous findings from analyses among commercially insured patients with DMD in the USA [ 12 ], the results of the primary (non-age-restricted) analyses reported slightly older median ages at the first observation of key clinical outcomes, compared with published estimates from clinical studies [ 4 8 ]. This suggests that the first observation for individual clinical outcomes in a cut of administrative health insurance claims data may not necessarily reflect an initial diagnosis of that milestone, but instead reflects the first captured event within the dataset.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Consistent with previous findings from analyses among commercially insured patients with DMD in the USA [ 12 ], the results of the primary (non-age-restricted) analyses reported slightly older median ages at the first observation of key clinical outcomes, compared with published estimates from clinical studies [ 4 8 ]. This suggests that the first observation for individual clinical outcomes in a cut of administrative health insurance claims data may not necessarily reflect an initial diagnosis of that milestone, but instead reflects the first captured event within the dataset.…”
Section: Discussionsupporting
confidence: 86%
“…The strengths of the study stem from the use of a well-validated dataset that provided a large sample size of patients with DMD, including children and adults over an average follow-up period of 3 years. The algorithm to identify the cohort was previously used in similar studies to understand clinical outcomes [ 12 , 13 , 25 , 26 ]. In addition, this study offers insights into the prevalence of key DMD outcomes observed among patients covered by Medicaid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations